Nucleotide sequence analysis of the spacer regions flanking the rat rRNA transcription unit and identification of repetitive elements. - Yavachev, L P (1986)
We investigated the organization of the rat rDNA non-transcribed spacer (NTS) by determining the sequence of large NTS segments located upstream (2501 bp) and downstream (4025 bp) from the rRNA transcription unit. We identified four B2-like and two ID mobile elements. They may be grouped in three pairs with the members of each pair located in the upstream and downstream NTS. The ID sequences are identical to the consensus sequence, while the pairs of B2-like elements show 85% and 50/65% homology to the consensus B2 sequence. The proximal part of the downstream NTS contains a region of widely diverged SalI tandem repeats. A considerable part of the analyzed upstream and downstream NTS sequences is constituted by different types of simple sequences and long poly(purine) X poly(pyrimidine) tracts. These data show that the rat rDNA NTS regions flanking the rRNA transcription unit are characterized by a combination of short interspersed (B2-superfamily) and various simple sequences.